1990
DOI: 10.1083/jcb.111.3.1089
|View full text |Cite
|
Sign up to set email alerts
|

Human endothelial actin-binding protein (ABP-280, nonmuscle filamin): a molecular leaf spring.

Abstract: Abstract. nonmuscle filamin) is a ubiquitous dimeric actin cross-linking phosphoprotein of peripheral cytoplasm, where it promotes orthogonal branching of actin filaments and links actin filaments to membrane glycoproteins. The complete nucleotide sequence of human endothelial cell ABP cDNA predicts a polypeptide subunit chain of 2,647 amino acids, corresponding to 280 kD, also the mass derived from physical measurements of the native protein. The actin-binding domain is near the amino-terminus of the subu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
482
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 484 publications
(498 citation statements)
references
References 61 publications
14
482
0
Order By: Relevance
“…The numbers on panel show fraction numbers. Asterisk and closed arrowhead indicate the components of 250 kDa (p250) and 160 kDa (p160), respectively (ABP-280) (Gorlin et al, 1990). These results showed that Rho-kinase has an activity for MRLC diphosphorylation in nonmuscle cells.…”
Section: Purification and Identification Of Rho-kinase As A Diphosphomentioning
confidence: 77%
“…The numbers on panel show fraction numbers. Asterisk and closed arrowhead indicate the components of 250 kDa (p250) and 160 kDa (p160), respectively (ABP-280) (Gorlin et al, 1990). These results showed that Rho-kinase has an activity for MRLC diphosphorylation in nonmuscle cells.…”
Section: Purification and Identification Of Rho-kinase As A Diphosphomentioning
confidence: 77%
“…Structurally filamins are homodimers with large polypeptide chains that associate at their C termini (24,25). Their conserved N-terminal actin-binding domains (ABD) 2 belong to the ABDs common to the members of the ␣-actinin/spectrin superfamily of actin-binding proteins (26,27).…”
mentioning
confidence: 99%
“…FLNA is a substrate for multiple kinases (reviewed in Sarkisian et al 2008) depending on whether or not its actin bound (Kawamoto and Hidaka 1984), with its cross-linking activity itself regulated by phosphorylation (Cukier et al 2007). FLN is a substrate for the Ca 2+ -activated protease calpain (Gorlin et al 1990) and for the ASB2 ubiquitin ligase (Heuze et al 2008) which provide irreversible regulatory mechanisms for severing FLN cross-links in processes requiring membrane and cytoskeleton remodelling such as cell migration (Marzia et al 2006;Baldassarre et al 2009) and receptor cycling (Seck et al 2003). FLN's role in cell motility and spreading appears to be cell-type dependent.…”
Section: Filamin Cellular Functionsmentioning
confidence: 99%
“…The hypothesis that FLN acts as a molecular spring was initially formulated upon sequence analysis of FLN domain structure (Gorlin et al 1990) with subsequent analysis of its biomechanical and structural properties showing it suited to a cellular role regulating both the organization and mechanics of F-actin networks. FLN is found in the F-actin rich region near cell membranes where fast remodelling of the cytoskeleton is required, e.g.…”
Section: Filamin Biomechanicsmentioning
confidence: 99%
See 1 more Smart Citation